Evaluation of methionine availability to dairy cowswhen added to mechanically extracted soybean mealwith soy gums - D.W. Brake; Evan C. Titgemeyer; Barry J. Bradford; C.A. Macgregor (Kansas Agricultural Experiment Station Research Reports, 2011)
Twenty-five Holstein cows were fed 5 different diets to evaluate amounts of metabolizable methionine provided to dairy cows from a mechanically extracted soybean meal (meSBM) with methionine added during manufacture. The control diet was designed to be deficient in metabolizable methionine supply. Two amounts of methionine were added from either a commercially available ruminally protected product (RPMet) or from a meSBM with methionine added during manufacture (meSBM-Met). Average milk yield was 98.8 lb/day, average milk fat was 2.81%, and milk urea nitrogen (MUN) averaged 8.6 mg/dL. Milk protein yield was not responsive to metabolizable methionine supply, suggesting that milk protein yield was not an optimal criterion for assessing metabolizable methionine supply. Milk protein content was greater when methionine was provided as RPMet than meSBM-Met. In addition, RPMet linearly increased plasma free methionine, but meSBM-Met did not. Body condition score (BCS; 1=thin and 5 =fat) was increased linearly by meSBM-Met, but responses were quadratic to RPMet. Methionine added to meSBM during manufacture did not appear to be available to dairy cows, likely because of extensive ruminal degradation.; Dairy Day, 2011, Kansas State University, Manhattan, KS, 2011; Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-176-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1057; Dairy; Methionine; Dairy cow; Soybean meal